Unlocking Scientific Reasoning through Ethno-STEM : Mapping the Research Landscape and Future Directions - Ina Ana Khoeriah; Della Apriyani Kusuma Putri; Andini Retno Yunitasari (Biocaster : Jurnal Kajian Biologi, 2026)
The stagnation of global scientific literacy scores, as highlighted by PISA results, necessitates a paradigm shift toward culturally responsive pedagogies that foster holistic competencies. This study investigates the global trends of Ethno-STEM integration in facilitating Scientific Reasoning and 6C Skills (Character, Citizenship, Collaboration, Communication, Creativity, and Critical Thinking) through the lens of deep learning. Employing a mixed-method approach combining Systematic Literature Review (SLR) with PRISMA protocol and bibliometric analysis, we analyzed 2889 documents from the Scopus database spanning 2015 to 2026. The findings reveal an exponential growth in publications, predominantly driven by Indonesia and the United States, indicating a shift from a "western-centric" to a localized science education approach. VOSviewer visualization unveils a critical thematic evolution: research focus has transitioned from mere documentation of indigenous knowledge (e.g., ethnobotany) to complex pedagogical interventions aiming at cognitive development and digital integration. Theoretically, Ethno-STEM serves as an "epistemological bridge," reducing cognitive dissonance between students' native science and school science. Practically, the study recommends transforming curricula by embedding local wisdom as a core context for Project-Based Learning (PjBL) to nurture high-order thinking. Future research directions highlight the need for integrating immersive technologies (AI/AR/VR) and conducting empirical studies to measure the direct impact of Ethno-STEM on scientific reasoning.